2016
DOI: 10.1136/gutjnl-2016-312608
|View full text |Cite
|
Sign up to set email alerts
|

Double somatic mutations in mismatch repair genes are frequent in colorectal cancer after Hodgkin's lymphoma treatment

Abstract: We have demonstrated a higher frequency of MSI among t-CRCs, which results from somatic MMR gene mutations. This suggests a novel association of somatic MMR gene mutations with prior anticancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 53 publications
2
38
3
Order By: Relevance
“…15,27 Second, especially in female HL survivors, we detected a high prevalence of serrated lesions and serrated polyposis syndrome. First, neoplastic lesions were more frequently located in the proximal colon in HL survivors in comparison with controls.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…15,27 Second, especially in female HL survivors, we detected a high prevalence of serrated lesions and serrated polyposis syndrome. First, neoplastic lesions were more frequently located in the proximal colon in HL survivors in comparison with controls.…”
Section: Discussionmentioning
confidence: 78%
“…15 These mutations could not be associated with a colonic region, sex, or a specific HL treatment. 15 These mutations could not be associated with a colonic region, sex, or a specific HL treatment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A difference in carcinogenesis has been suggested only for therapy‐related colorectal cancer diagnosed in HL survivors, as these tumors are more frequently microsatellite instable due to somatic mutations in mismatch repair genes . In therapy‐related esophageal cancer compared with sporadic cancer, no difference in frequency of microsatellite instability or loss of heterozygosity was found .…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][9][10][11] A few studies suggest a difference in clinical and histopathological characteristics of GI cancer in HL survivors compared with first primary GI cancer. [12][13][14] To our knowledge, only one previous study examined survival of GI cancer in HL survivors and reported a worse overall survival in subgroups of HL survivors compared with first primary GI cancer patients, that is, those diagnosed with TNM stage IIB-IV colon cancer and a small group (N = 8) of TNM stage I gastric cancer. 13 No differences in disease-specific survival were found.…”
Section: Introductionmentioning
confidence: 99%